Textile technology students' perception towards theapplication of vector ruler as a teaching tool inlearning introductory physics / Amin Aadenan ...[et al.] - Aadenan, Amin; Jaafar, Nor Fadhlin; Makhtar, Nurulizzati; Abdullah, Siti Zaubidah (Universiti Teknologi MARA Cawangan Pahang, 2020)
This paper presents the application of a teaching tool called "Vector Ruler (VR)" on the Textile Technology students' perception in learning Introductory Physics. The main objective of this study is to identify the effectiveness of utilizing Vector Ruler in teaching and learning Introductory Physics on non-major students based on their perspectives and learning preferences. The purpose is to overcome their difficulties in understanding the fundamental physics concepts and to provide an insight to educators on the importance of teaching and learning strategies to be developed and employed by them. The study was conducted using ADDIE model as a main framework on the first year students enrolled into the Diploma in Textile Technology at Universiti Teknologi MARA (UiTM) Negeri Sembilan, Kuala Pilah Campus for the Academic Year of 2019-2020. Based on the results obtained, majority of the students agreed with the utilization of Vector Ruler as a teaching tool is considerably useful in teaching and learning Introductory Physics where all the responses are above the average. In addition, the majority of the students strongly agreed that their desire to learn Introductory Physics is high if lecturers integrate the use of teaching tool during lecture. This concludes that most students agreed that the combination of using a teaching tool with the traditional teaching methods is an alternative way to improve their motivation, understanding and visualization. Thus, offers an insight for educators to diversify their teaching methods based on the non-major students' preferences.